Functional interactions between transient receptor potential M8 and transient receptor potential V1 in the trigeminal system: Relevance to migraine pathophysiology. (April 2018) - Kayama, Yohei; Shibata, Mamoru; Takizawa, Tsubasa; Ibata, Keiji; Shimizu, Toshihiko; Ebine, Taeko; Toriumi, Haruki; Yuzaki, Michisuke; Suzuki, Norihiro
Background: Recent genome-wide association studies have identified transient receptor potential M8 ( TRPM8 ) as a migraine susceptibility gene. TRPM8 is a nonselective cation channel that mediates cool perception. However, its precise role in migraine pathophysiology is elusive. Transient receptor potential V1 (TRPV1) is a nonselective cation channel activated by noxious heat. Both TRPM8 and TRPV1 are expressed in trigeminal ganglion (TG) neurons. Methods: We investigated the functional roles of TRPM8 and TRPV1 in a meningeal inflammation-based migraine model by measuring the effects of facial TRPM8 activation on thermal allodynia and assessing receptor coexpression changes in TG neurons. We performed retrograde tracer labeling to identify TG neurons innervating the face and dura. Results: We found that pharmacological TRPM8 activation reversed the meningeal inflammation-induced lowering of the facial heat pain threshold, an effect abolished by genetic ablation of TRPM8. No significant changes in the heat pain threshold were seen in sham-operated animals. Meningeal inflammation caused dynamic alterations in TRPM8/TRPV1 coexpression patterns in TG neurons, and colocalization was most pronounced when the ameliorating effect of TRPM8 activation on thermal allodynia was maximal. Our tracer assay disclosed the presence of dura-innervating TG neurons sending collaterals to the face. Approximately half of them were TRPV1-positive. We also demonstrated functional inhibition of TRPV1 by TRPM8 in a cell-based assay using c-Jun N-terminal kinase phosphorylation as a surrogate marker. Conclusions: Our findings provide a plausible mechanism to explain how facial TRPM8 activation can relieve migraine by suppressing TRPV1 activity. Facial TRPM8 appears to be a promising therapeutic target for migraine.